Prof S N Dasgupta Memorial Lecture - Phytophthora cactorum - A threateningpathogen of apple - GUPTA, V.K. (Indian Phytopathology, 2002)
A review of P. cactorum infection on apples is presented. Sections covered are: symptomatology; biology of the pathogen; epidemiology; development of a technique for field testing; and disease management.